Association of Daily Eating Duration and Day-To-Day Variability in the Timing of Eating With Fatal Cancer Risk in Older Men - Meth, Elisa M. S.; van Egmond, Lieve T.; Moulin, Thiago C.; Cedernaes, Jonathan; Rosqvist, Fredrik; Benedict, Christian (Frontiers in Nutrition, 2022)
Meal timing has significant effects on health. However, whether meal timing is associated with the risk of developing and dying of cancer is not well-researched in humans. In the present study, we used data from 941 community-dwelling men aged 71 years who participated in the Uppsala Longitudinal Study of Adult Men to examine the association of meal timing with cancer morbidity and fatal cancer. The following meal timing variables were derived from seven-day food diaries: i) daily eating duration, i.e., the time between the first and last eating episode of an arbitrary day; ii) the calorically weighted midpoint of the daily eating interval, a proxy of when the eating window typically occurs during an arbitrary day; and iii) the day-to-day variability in the timing of eating. We also assessed the reported daily energy intake reliability using the Goldberg method. During a mean observational period of 13.4 years, 277 men (29.4%) were diagnosed with cancer. Furthermore, 191 men (20%) died from cancer during 14.7 years of follow-up. As shown by Cox regression adjusted for potential confounders (e.g., smoking status and daily energy intake), men with reliable dietary reports whose daily eating intervals were on average 13 hours long had a 2.3-fold greater fatal cancer risk than men whose daily eating windows were on average about 11 hours long. We also found that men with an average day-to-day variability in the timing of eating of 48 to 74 minutes had a 2- to 2.2-fold higher fatal cancer risk than those with the lowest average day-to-day variability in the timing of eating (i.e., 23 minutes). No clear associations were found in men with inadequate dietary reports, emphasizing the need to consider the reliability of dietary records in nutritional epidemiology. To fully unlock its potential, studies are needed to test whether recommendations to time-restrict the 24-h eating interval and reduce day-to-day variability in the timing of eating can meaningfully alter the risk of death due to cancer.